Multicentre study on the accuracy of lung ultrasound in the diagnosis and monitoring of respiratory sequelae in the medium and long term in patients with COVID-19 - Ramos Hernández, Cristina; Tilve Gomez, Amara; Sánchez Fernández, Ana; Cordovilla, Rosa; Núñez Ares, Ana; Ordoñez Gómez, Paola; Wangüemert Pérez, Aurelio; Castro Anón, Olalla; González Ramírez, Jorge; Valdivia Salas, Mar; Pérez Pallares, Javier; Ferrer Pargada, Diego; et al. (Frontiers in Medicine, 2023)
Introduction Lung ultrasound (LUS) has proven to be a more sensitive tool than radiography (X-ray) to detect alveolar-interstitial involvement in COVID-19 pneumonia. However, its usefulness in the detection of possible pulmonary alterations after overcoming the acute phase of COVID-19 is unknown. In this study we proposed studying the utility of LUS in the medium- and long-term follow-up of a cohort of patients hospitalized with COVID-19 pneumonia. Materials and methods This was a prospective, multicentre study that included patients, aged over 18 years, at 3 ± 1 and 12 ± 1 months after discharge after treatment for COVID-19 pneumonia. Demographic variables, the disease severity, and analytical, radiographic, and functional clinical details were collected. LUS was performed at each visit and 14 areas were evaluated and classified with a scoring system whose global sum was referred to as the “lung score.” Two-dimensional shear wave elastography (2D-SWE) was performed in 2 anterior areas and in 2 posterior areas in a subgroup of patients. The results were compared with high-resolution computed tomography (CT) images reported by an expert radiologist. Results A total of 233 patients were included, of whom 76 (32.6%) required Intensive Care Unit (ICU) admission; 58 (24.9%) of them were intubated and non-invasive respiratory support was also necessary in 58 cases (24.9%). Compared with the results from CT images, when performed in the medium term, LUS showed a sensitivity (S) of 89.7%, specificity (E) 50%, and an area under the curve (AUC) of 78.8%, while the diagnostic usefulness of X-ray showed an S of 78% and E of 47%. Most of the patients improved in the long-term evaluation, with LUS showing an efficacy with an S of 76% and E of 74%, while the X-ray presented an S of 71% and E of 50%. 2D-SWE data were available in 108 (61.7%) patients, in whom we found a non-significant tendency toward the presentation of a higher shear wave velocity among those who developed interstitial alterations, with a median kPa of 22.76 ± 15.49) versus 19.45 ± 11.39; p = 0.1). Conclusion Lung ultrasound could be implemented as a first-line procedure in the evaluation of interstitial lung sequelae after COVID-19 pneumonia.